Microsoft Dynamics AX 2012 R3 development cookbook : over 80 effective recipes to help you solve real-world Microsoft Dynamics AX development problems /: over 80 effective recipes to help you solve real-world Microsoft Dynamics AX development problems. (2015) - Pocius, Mindaugas
No abstract available